2020
DOI: 10.1021/acs.est.9b06026
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Organophosphate Flame Retardants and the Risk of Low Birth Weight: A Nested Case-Control Study in China

Abstract: Organophosphate flame retardants (OPFRs), used as flame retardants and plasticizers, have been suggested to impair fetal growth and development in toxicological studies, but epidemiological data are extremely limited. This study was designed to explore whether prenatal exposure to OPFRs was associated with an increased risk of low birth weight (LBW) using a nested case-control design based on the ongoing prospective birth cohort in Wuhan, China. A total of 113 cases and 226 matched controls recruited from this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
47
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 61 publications
7
47
1
Order By: Relevance
“…These ndings are consistent with several other epidemiologic studies that indicate a potential link between OPE exposure and altered fetal growth (22,23). For example, a recent prospective case-control study of low birth weight (n = 339) based in China reported that the odds of low birth weight in women with the highest tertile of urinary DPhP was 4.62 (95% CI: 1.72, 12.40) times that observed in the lowest tertile (22). Notably, concentrations of DPhP and BDCPP were higher in our cohort (DPhP median = 0.74 ng/mL, BDCPP median = 0.67 ng/mL) compared to the Chinese cohort (DPhP median = 0.05 ng/mL, BDCPP median = 0.05 ng/mL) (22).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These ndings are consistent with several other epidemiologic studies that indicate a potential link between OPE exposure and altered fetal growth (22,23). For example, a recent prospective case-control study of low birth weight (n = 339) based in China reported that the odds of low birth weight in women with the highest tertile of urinary DPhP was 4.62 (95% CI: 1.72, 12.40) times that observed in the lowest tertile (22). Notably, concentrations of DPhP and BDCPP were higher in our cohort (DPhP median = 0.74 ng/mL, BDCPP median = 0.67 ng/mL) compared to the Chinese cohort (DPhP median = 0.05 ng/mL, BDCPP median = 0.05 ng/mL) (22).…”
Section: Discussionsupporting
confidence: 92%
“…We observed that levels of urinary DPhP as well as the mixture of OPE metabolites were associated with reduced odds of LGA births although there was no association with SGA. These ndings are consistent with several other epidemiologic studies that indicate a potential link between OPE exposure and altered fetal growth (22,23). For example, a recent prospective case-control study of low birth weight (n = 339) based in China reported that the odds of low birth weight in women with the highest tertile of urinary DPhP was 4.62 (95% CI: 1.72, 12.40) times that observed in the lowest tertile (22).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We observed that levels of urinary DPhP as well as the mixture of OPE metabolites were associated with reduced odds of LGA births (i.e., lower birth weight) although there was no association with SGA. These ndings are consistent with two other epidemiologic studies that indicate a potential link between OPE exposure and altered fetal growth (17,18). For example, a recent prospective case-control study of low birth weight (n = 339) based in China reported that the odds of low birth weight in women with the highest tertile of urinary DPhP was 4.62 (95% CI: 1.72, 12.40) times that observed in the lowest tertile (17).…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, the literature linking consumer product chemicals with altered fetal growth is highly inconsistent (1). These inconsistencies may be the result of differences in study design (17,18), timing and frequency of exposure assessment (19)(20)(21), and the metrics used to monitor and de ne fetal growth outcomes (22)(23)(24). In addition to these considerations, pregnant women are exposed to highly complex mixtures of consumer product chemicals (25,26).…”
Section: Introductionmentioning
confidence: 99%